A comparison of oral feeding and total parenteral nutrition in infants of very low birth mass - Higgs, Stephen Charles (Department of Paediatrics and Child Health, 2020)
This work was car'red out in the Neonatal Intensive Care Unit at Groote Schuur Hospital, Cape Town, from July, 1972, to December, 1973, under the guidance of Dr. A.F. Malan. This was a newly opened Unit for Coloured and African Neonates requiring special care, well-equipped with trained staff and good monitoring apparatus. For the first time it was possible to provide facilities for patient care in line with those available abroad. The problem of feeding preterm infants has interested many authors (Abramowicz, 1966; Babson, 1971; Gamsu, 1972). The ideal quantity, content of nutrients, calorific value and mode of administration of feeds remains, at best, approximate. With the advent of Total Parenteral Nutrition (TPN) and the availability of relatively safe solutions of fats and amino-acids for intravenous use, interest has been stimulated in the optimal nutrient and caloric requirements of the growing infant.